Activated autophagy of innate immune cells during the early stages of major trauma - Chen, Deng; Zhang, Cong; Luo, Jialiu; Deng, Hai; Yang, Jingzhi; Chen, Shunyao; Zhang, Peidong; Dong, Liming; Chang, Teding; Tang, Zhao-hui (Frontiers in Immunology, 2023)
Background Trauma-induced immune dysfunction has been a major barrier to achieving reduced mortality, which is poorly understood. Autophagy is a crucial catabolic mechanism of immune cells during times of stress. Few studies have investigated the immune regulatory effects induced by autophagy after trauma. Here, we use single-cell transcriptomics analysis in a major trauma cohort to demonstrate the dominant role of autophagy in innate immune cells during the early stages of major trauma. Method Single-cell transcriptional profiling of peripheral blood mononuclear cells (PBMCs) was performed, which were sampled from three control participants and five major trauma patients within 6 hours of injury. In detail, after single-cell RNA-sequence data processing, cell type annotation and cluster marker identification were performed. A genetic toolbox with 604 autophagy-related genes was used to monitor the autophagy levels in immune cells. In addition, all transcriptome RNA sequencing data obtained from PBMCs in a cohort of 167 major trauma patients were downloaded from gene expression omnibus (GEO) datasets (GSE36809). Key deregulated biological processes and important autophagic hub genes involved in immune cells were identified by weighted gene co-expression network analysis and gene ontology enrichment analysis. Results A total of 20,445 differentially expressed genes were identified and five co-expression modules were constructed. Enrichment analysis indicated that activated autophagy is the most important biological process during the early stages of major trauma, and JMY (autophagy-related genes) were identified as hub genes. The single-cell transcriptional profiling of PBMCs demonstrated that all components of adaptive immune cells were significantly decreased, whereas components of innate immune cells (monocytes and neutrophils) were significantly increased in major trauma patients compared with control participants. Activated autophagy was detected in monocytes and neutrophils by monitoring the dynamic transcriptional signature of the autophagy-related genetic toolbox. Biological process analysis shows that antigen uptake, processing presentation, and major histocompatibility complex (MHC) class II protein complex assembly pathways were up-regulated in autophagy-positive monocytes, whereas antigen processing and presentation of endogenous antigen and type I interferon signaling pathways were up-regulated in autophagy-positive neutrophils during the early stages of major trauma. Conclusion Our study demonstrated that autophagy is a biological process crucial to the development of immune disorders in the early stages of major trauma. Furthermore, the results of our study generated a comprehensive single-cell immune landscape for major trauma patients, in which we determined that autophagy profoundly affects the main functions of innate immune cells and provides insight into the cellular basis of immune dysregulation after major trauma.